Response of rice breeding lines to Nfertilizer application - Ajala, S.O.; Masajo, T.M.; Winslow, M.D. (2009)
Advanced rice breeding lines were evaluated in eight environments (two seasons and four N-fertilizer levels) to investigate the effectiveness of selecting genotypes for less favorable low fertilizer input environments. Highly significant Environment (E), Genotype (G) and G x E. interaction effects were obtained for grain yield revealed that for genotypes that were better adapted to less favourable environments were also stable and would do well with very low(40k9 N/ha) fertilizer input.